Polimorfismo na produção de medicamentos - de Araujo, Gabriel Lima Barros; Pitaluga Jr., Altivo; Antonio, Selma Gutierrez [UNESP]; Santos, Carlos de Oliveira Paiva; Matos, Jivaldo do Rosário (My University, 2012)
Polymorphism can cause quality deviations during the production of medicines and can influence their effectiveness. Therefore, an understanding of this phenomenon and its implications opens a wide field of possibilities to be explored in the pharmaceutical field, including the emergence of new paradigms and tools for the quality assurance of medicines. This paper presents an introduction to basic aspects of the polymorphism phenomenon and its implications for the production and control of medicines, with emphasis on drug polymorphs.

O polimorfismo pode ocasionar desvios de qualidade durante o processo produtivo e influenciar o desempenho dos medicamentos. Por isso, o entendimento do fenômeno e suas implicações abre um campo amplo de possibilidades a serem exploradas na área farmacêutica, incluindo o surgimento de novos paradigmas e ferramentas na garantia da qualidade de medicamentos. Este trabalho apresenta uma introdução aos aspectos básicos do fenômeno do polimorfismo e suas implicações na produção e controle de medicamentos, com ênfase no polimorfismo dos fármacos. Palavras-chave: Polimorfismo de fármacos. Caracterização no estado sólido. Cristalografia de policristais. ABSTRACT Polymorphism can cause quality deviations during the production of medicines and can influence their effectiveness. Therefore, an understanding of this phenomenon and its implications opens a wide field of possibilities to be explored in the pharmaceutical field, including the emergence of new paradigms and tools for the quality assurance of medicines. This paper presents an introduction to basic aspects of the polymorphism phenomenon and its implications for the production and control of medicines, with emphasis on drug polymorphs. Keywords: Polymorphism of drugs. Solid State Characterization. Crystallography of Polycrystals.
Polymorphism in the manufacture of medicines
Keywords: Crystallography of Polycrystals; Polymorphism of drugs; Solid State Characterization; drug industry; quality control